Rapid protection against viral infections by chemokine-accelerated post-exposure vaccination - Annkristin Heine; Annkristin Heine; Niels A. W. Lemmermann; Niels A. W. Lemmermann; Chrystel Flores; Chrystel Flores; Janine Becker-Gotot; Natalio Garbi; Peter Brossart; Christian Kurts; Christian Kurts (Frontiers in Immunology, 2024)
IntroductionProphylactic vaccines generate strong and durable immunity to avoid future infections, whereas post-exposure vaccinations are intended to establish rapid protection against already ongoing infections. Antiviral cytotoxic CD8+ T cells (CTL) are activated by dendritic cells (DCs), which themselves must be activated by adjuvants to express costimulatory molecules and so-called signal 0-chemokines that attract naive CTL to the DCs.HypothesisHere we asked whether a vaccination protocol that combines two adjuvants, a toll-like receptor ligand (TLR) and a natural killer T cell activator, to induce two signal 0 chemokines, synergistically accelerates CTL activation.MethodsWe used a well-characterized vaccination model based on the model antigen ovalbumin, the TLR9 ligand CpG and the NKT cell ligand α-galactosylceramide to induce signal 0-chemokines. Exploiting this vaccination model, we studied detailed T cell kinetics and T cell profiling in different in vivo mouse models of viral infection.ResultsWe found that CTL induced by both adjuvants obtained a head-start that allowed them to functionally differentiate further and generate higher numbers of protective CTL 1-2 days earlier. Such signal 0-optimized post-exposure vaccination hastened clearance of experimental adenovirus and cytomegalovirus infections.ConclusionOur findings show that signal 0 chemokine-inducing adjuvant combinations gain time in the race against rapidly replicating microbes, which may be especially useful in post-exposure vaccination settings during viral epi/pandemics.